TINGKAT PENGETAHUAN DAN SIKAP WANITA USIA SUBUR DENGAN MINAT UNTUK MELAKUKAN VAKSINASI HPV (HUMAN PAPILLOMA VIRUS) - Wahyuni, Nita Tri; Kumala, Anes Patria (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
One of the causes of death that is quite high in the world is cancer. Cervical cancer or cervical cancer is a malignancy that occurs from the cells of the cervix. Cervical cancer is one of the gynecological cancers that can be prevented by making early detection efforts, namely a fairly high prevalence in the community, long disease development, and specific examination techniques have been found, and there are effective treatments. The number of cancer patients in the world in 2020 reached 19.3 million cases, the most suffered were breast cancer as much as 11.7 percent, then lung cancer 11.4 percent, colon or rectal cancer 10 percent and cervical cancer 7.3 percent. The number of cervical cancer patients in Indonesia is 36,633 cases, the second largest number after breast cancer. The main cause of cervical cancer is not known with certainty but more often due to Human Papilloma Virus (HPV) infection. The type of research used in this study is descriptive analytic with Cross Sectional design which aims to determine the relationship between knowledge and attitudes with interest in HPV vaccination in the Susukan Area, East Jakarta. The results showed that the level of knowledge and attitude towards HPV vaccination was quite good